2022
DOI: 10.1093/psyrad/kkac002
|View full text |Cite
|
Sign up to set email alerts
|

The inter-relationships of the neural basis of rumination and inhibitory control: neuroimaging-based meta-analyses

Abstract: Rumination, as a clinical manifestation and pathogenic factor of depression, has long been the focus of psychological research regarding its causes and ameliorating approaches. Behavioral studies have shown that rumination is related to inhibitory control deficits, which provides ideas for reducing it. However, the neural relationship between them has not been clearly discussed. In this study, we first used multi-level kernel density analysis to conduct two meta-analyses of published functional magnetic resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 81 publications
1
12
0
Order By: Relevance
“…In line with these results, the seminal neurovisceral integration model proposes that in healthy individuals, the prefrontal cortex is in control over subcortical areas, resulting in tonic inhibitory control of the parasympathetic branch of the ANS (i.e., higher HRV; Thayer & Lane, 2009). As a result, these neural and autonomic regulations result in less viscous cycles of ruminative thoughts and turn higher resting HRV (Song et al, 2022). However, in the current study, this association between the tendency to ruminate and baseline vagally-mediated HRV measured at rest cannot be observed in healthy individuals, even after controlling for gender, age, and the level of depressive symptoms.…”
Section: Discussionmentioning
confidence: 89%
“…In line with these results, the seminal neurovisceral integration model proposes that in healthy individuals, the prefrontal cortex is in control over subcortical areas, resulting in tonic inhibitory control of the parasympathetic branch of the ANS (i.e., higher HRV; Thayer & Lane, 2009). As a result, these neural and autonomic regulations result in less viscous cycles of ruminative thoughts and turn higher resting HRV (Song et al, 2022). However, in the current study, this association between the tendency to ruminate and baseline vagally-mediated HRV measured at rest cannot be observed in healthy individuals, even after controlling for gender, age, and the level of depressive symptoms.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, rumination is characterized by the failure of cognitive control over the past events and is related to negative cognition (Ciesla & Roberts, 2007;Watkins & Roberts, 2020). Recently, Song et al (2022) found that rumination and inhibitory control overlapped in brain regions (e.g., prefrontal cortex, which is involved in higherorder executive function), supporting the conclusion of behavior studies that rumination is related to inhibitory control (Ballesio et al, 2019;Zhou et al, 2020).…”
Section: The Relationship Of Forgiveness→rumination→self-control and ...mentioning
confidence: 84%
“…The rACC as an important node in the VMN receives a dense dopaminergic innervation 40 related to emotional processes and attentional control, and potentiated responses of this region may contribute to abnormal responses to negative feedback in individuals with elevated negative affect, including anxiety and depressive symptoms 41 . The DMN, also called the self‐directed network, is responsible for self‐awareness, emotion, rumination and so forth 42 . Accumulating evidence has shown that both the parahippocampal and ICC are core components of the DMN associated with self‐related decision‐making 43 and the processing of human emotion 44,45 .…”
Section: Discussionmentioning
confidence: 99%